The neighbors of Casas Grandes : excavating medio period communities of northwest Chihuahua, Mexico - Whalen, Michael E. (University of Arizona Press, 2009)
Casas Grandes, or Paquimé, in northwestern Mexico was of one of the few socially complex prehistoric civilizations in North America. Now, based on more than a decade of surveys, excavations, and field work, this text looks at Casas Grandes and its surrounding communities in The Neighbors of Casas Grandes. This volume provides a look into the culture of the Casas Grandes area, involving not just the research of the architecture and artifacts left behind but also the ecology of the area. The authorsu2019 research reveals the complex relationship Casas Grandes had with its neighbors, varying from very direct contact with some communities to more indirect links with others. Important internal influences on the areau2019s development come to light and population sizes throughout the period demonstrate the absorption of the surrounding populations into Casas Grandes as it reached the peak of its power in the region.